Analysis of Visible Light Communication Link's Performance in Fire Smoke Environment. (26th May 2021) - Yang, Yu-Feng; Chang, Kang-Kang; Ci, Ying
Abstract : This paper mainly studies the communication performance of visible light communication link in fire smoke environment. Compared with the previous studies, this study no longer only considers a single wavelength and considers the influence of smoke and background light noise. Firstly, the variation of background light noise caused by sunlight during a day was analyzed, then signal-to-noise ratio (SNR) and bit error rate (BER) of the visible light communication link in fire smoke environment with different visibility were calculated, and finally, the variation of received power with the angle β between the LED optical axis and the communication link (from LED to receiver) was analyzed. The results show that, during a day from 07:00 to 18:30, background light noise first increases and then decreases, BER changes in the same trend and reaches the maximum at about 13:00, while SNR changes in the opposite trend and reaches the minimum at about 13:00. When visibility is 100 m, the maximum difference of SNR between 7:00 and 13:00 is about 19 dB, and the maximum difference of BER is about 5.3E-10. At 7:00, the maximum difference of SNR is about 13 dB between the visibility of 1 m and the visibility of 100 m, and the maximum difference of BER is about 1.44 E − 11, and received power decreases with the increase of β . In addition, SNR increases with visibility of fire smoke environment, and BER changes in the opposite trend. Lastly, in order to enhance the performance of visible light communication in fire smoke environment, this paper gives the transmitting power scheme.